2021
DOI: 10.1109/jstars.2021.3113658
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Image Super-Resolution via Residual Aggregation and Split Attentional Fusion Network

Abstract: Remote sensing images contain various land surface scenes and different scales of ground objects, which greatly increases the difficulty of super-resolution tasks. The existing deep learning-based methods cannot solve this problem well. To achieve high-quality super-resolution of remote sensing images, a residual aggregation and split attentional fusion network (RASAF) is proposed in this article. It is mainly divided into the following three parts. First, a split attentional fusion block is proposed. It uses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Wang et al [43] construct a lightweight feature enhancement network to achieve a good trade-off between model complexity and performance for remote sensing images. Chen et al [15] propose a U-Net like network combined with a split attentional fusion model to obtain HR remote sensing images. Moreover, GAN is also introduced to improve the visual super-resolved results for remote sensing LR images.…”
Section: A Deep Learning Based Remote Sensing Image Srmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [43] construct a lightweight feature enhancement network to achieve a good trade-off between model complexity and performance for remote sensing images. Chen et al [15] propose a U-Net like network combined with a split attentional fusion model to obtain HR remote sensing images. Moreover, GAN is also introduced to improve the visual super-resolved results for remote sensing LR images.…”
Section: A Deep Learning Based Remote Sensing Image Srmentioning
confidence: 99%
“…I MAGE super-resolution (SR), as a vital technique for elevating image and video spatial resolution, has found vast applications in medical imaging [1,2], surveillance and security [3,4], and remote sensing image analysis [5][6][7], etc. Particularly, remote sensing applications including object detection and recognition [8][9][10][11], semantic segmentation [12][13][14], and change detection [15] require high-resolution (HR) images with rich high-frequency details and texture information to perform effective image discrimination, analysis, interpretation, and perception. In face of the forbidden cost in image acquisition, SR becomes indispensable for remote sensing image applications.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, attention mechanism was introduced to the field of remote sensing image SR. HSENet [28] exploits the single-scale and cross-scale self-similarity information using multi-scale Non-Local attention. A split attention fusion block was established by Chen et al [2] allowing the method to adapt to varied multi-scale land surface reconstructions. Rather of exploring first-order attention (channel or spatial statistics), Zhang et al [29] advocated a high-order attention block to restore the missing details.…”
Section: B Remote Sensing Image Super-resolutionmentioning
confidence: 99%
“…Some recent work has initiated efforts in this direction. Residual aggregation and split attention fusion network [2] uses a UNet-based encoder and decoder structure to extract both shallow semantic information and high-level features. Although this approach is capable of extracting multi-scale features, it leads to irreversible information loss through frequent up and down sampling, which will eventually affect the reconstruction results.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that deep learning has achieved remarkable results in the fields of single-source remote sensing image (e.g., HSI, MSI, LiDAR, etc.) classification [18][19][20], semantic segmentation [21][22], and super-resolution [23]. In order to fully utilize the complementary information of multimodal remote sensing images, many excellent deep learning methods have been proposed, and typical models include convolutional neural networks (CNN), recurrent neural networks, and autoencoder networks.…”
mentioning
confidence: 99%